THE SOURCES OF CAPITAL SURPLUS. - Marple, Raymond P. (The Accounting Review, 1934)
Abstract This article focuses on the sources of capital surplus. Capital surplus may be defined as an excess of contributed capital over legal capital. American courts have developed many theories, among them the "trust fund," "the fraud," and the "holding-out" doctrines, to support the established rule that the legal capital of a corporation may not be reduced except through formal amendment of the corporate charter or as a result of operating losses in excess of accumulated surplus. In the eyes of the law any net worth in excess of legal capital is surplus, and in the absence of statutory provisions to the contrary, may be used by the board of directors for any desired purpose. These concepts of contributed capital and legal capital are of fundamental importance to the accountant. It seems hardly necessary to emphasize before a group of accountants the importance of distinguishing between contributed capital and earned capital. But to the lawyer and the courts, legal capital is the important fact, and no matter how much the accountant disapproves of certain legal definitions of capital he must recognize that the force of law makes them facts, and that these facts should be shown on his financial statements.